2007
DOI: 10.1007/s00330-007-0683-1
|View full text |Cite
|
Sign up to set email alerts
|

Liver, bone marrow, pancreas and pituitary gland iron overload in young and adult thalassemic patients: a T2 relaxometry study

Abstract: Thirty-seven patients with beta-thalassemia major, including 14 adolescents (15.2 +/- 3.0 years) and 23 adults (26.4 +/- 6.9 years), were studied. T2 relaxation time (T2) of the liver, bone marrow, pancreas and pituitary gland was measured in a 1.5-Tesla magnetic resonance (MR) imager, using a multiecho spin-echo sequence (TR/TE 2,000/20, 40, 60, 80, 100, 120, 140, 160 ms). Pituitary gland height was evaluated in a midline sagittal scan of a spin-echo sequence (TR/TE, 500/20 ms). The T2 of the pituitary gland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
1
4

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 34 publications
7
58
1
4
Order By: Relevance
“…For the pancreatic evaluation we did not apply fat saturation, used by Schwenzer et al (8). In fact, Argyropoulou et al suggested that the T 2 relaxation time depends not only on siderosis but also on the fatty infiltration of the pancreatic parenchyma (10). The multiecho sequence used in this study (10 echoes in-and out-phase) may reduce the influence of the signal fluctuation due to fat-parenchymal interface (11).…”
Section: Discussionmentioning
confidence: 96%
“…For the pancreatic evaluation we did not apply fat saturation, used by Schwenzer et al (8). In fact, Argyropoulou et al suggested that the T 2 relaxation time depends not only on siderosis but also on the fatty infiltration of the pancreatic parenchyma (10). The multiecho sequence used in this study (10 echoes in-and out-phase) may reduce the influence of the signal fluctuation due to fat-parenchymal interface (11).…”
Section: Discussionmentioning
confidence: 96%
“…31 This is not in contradiction with the results of the current study because ferritin does not cross the blood-brain barrier; therefore, its serum levels are not a good index of brain iron burden. 18,32 Although iron is critical in brain metabolism, increased iron deposition occurs in brain areas undergoing degeneration. 9,17,33 According to the currently accepted model of functional neuroanatomy, the globus pallidus external, through excitatory D2 receptors, receives GABAergic inhibitory projections from the striatum, and the STN receives GABAergic inhibitory projections from the globus pallidus external and strong excitatory glutamatergic afferents from the motor cortex.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 There is currently little literature reporting normative data for R2. 7,22 Additionally, we aimed to supplement current pituitary volume literature [14][15][16] by deriving sex-appropriate z-score calculations for pediatric and adult controls.…”
Section: Discussionmentioning
confidence: 99%